Lu Xiujing's Shoudu yi 授度儀: a grammatical reading. Issue 1 (2nd January 2018) - Lagerwey, John
ABSTRACT: Ritual, like any language, has its own grammar and, like spoken languages, we can get at that grammar by breaking the ritual down into its smallest component parts, which I call ritèmes. As phonemes are combined to form words, ritèmes are combined to form ritual acts, which are in turn combined to form 'sentences'. Ritual sentences are frequently composed of three parts, which I refer to as introductory (or preparatory), efficacious and conclusive. These ritual sentences are in their turn incorporated into the overarching framework of rites, and these rites into the ritual. Analysis in the present article focuses on the overarching framework of rites, which I describe as organized with asymmetrical symmetry: the symmetry provides the basic structure, the asymmetry the dynamic vector of the ritual. Complexity of structure of individual rites is the first key to the overall meaning of the ritual, transformational grammar of the ritèmes the second.